O ensino do gênero crônica no livro didático de português - Silvana Maria Santana (Universidade do Estado do Rio Grande do Norte, 2014)
The teaching guided by conception of language as social interaction has highlighted in the theoretical methodological orientation of current textbook. This study aims to examine how the textbook Portuguese Language: language and interaction directs the teaching of chronicle genre. For this purpose, this work relies on the conception language of sociodiscursiva. The methodology of this study was based on the selection of the textbook that brought presupposition the teaching conception as social interaction. The results showed that the study of chronicle directed to meet the intent of the enunciator and dialogue between texts. However, the social function of the genre and his the relation with the extraverbal were not verified. Furthermore, this didactics collection gave priority just the teaching reading. Therefore, did not present a significant proposal for teaching of the genre as social practice.